Plant Growth-Promoting Activity of Bacillus sp. PG-8 Isolated From Fermented Panchagavya and Its Effect on the Growth of Arachis hypogea - Gohil, Rinkal B.; Raval, Vikram H.; Panchal, Rakeshkumar R.; Rajput, Kiransinh N. (Frontiers in Agronomy, 2022)
A natural bacterial isolate showing multiple plant growth-promoting activities were isolated from fermented panchagavya (a mixture of five indigenous cow products). It is a Gram-positive, endospore-forming bacteria identified as Bacillus sp. PG-8 by 16S rRNA gene sequencing. The Bacillus sp. PG-8 have shown multiple plant growth-promoting activities as indole acetic acid (2.78 µg/ml), gibberellic acid (0.7 mg/ml), ammonia (6.51 µmol/ml), exopolysaccharide (2.6% w/v) production and phosphate solubilization (198.27 µg/ml). The Bacillus sp. PG-8 has ability to survive under the abiotic stress conditions like temperature (28-46°C), pH (5.0-12.0), salt (0.5-20.0% w/v NaCl), and osmotic resistance (1-10% w/v PEG-6000). Due to its diverse characteristics, the effect of Bacillus sp. PG-8 was tested on Arachis hypogea (Ground nut). The seeds treated with Bacillus sp. PG-8 demonstrated a 70% germination rate with seedling vigour indexes of 154. In pot study, Arachis hypogea growth showed 1.38, 1.38, 1.32, 1.39, 1.52 times increase in root hair number, leaf numbers, leaf width, leaf length and leaf area, respectively. The addition of Bacillus sp. PG-8 culture to the Arachis hypogea plant resulted in a significant improvement in plant growth. Bacillus sp. PG-8 is a spore producer with stress tolerance and multiple plant growth-promoting properties, making it a potential liquid biofertilizer candidate.